The Apheis project: Air Pollution and Health—A European Information System - Medina, Sylvia (Springer Netherlands, 2009)
At a time when the Health Effects Institute, Centers for Disease Control, and Environmental Protection Agency are creating an Environmental Public Health Tracking Program on Air Pollution Effects in the USA, it seemed useful to share the experience acquired since 1999 by the Apheis project (Air Pollution and Health—A European Information System), which has tracked the effects of air pollution on health in 26 European cities and continues to do so as the new Aphekom project. In particular, this paper first describes the continuing impact of air pollution on health in Europe, how the Apheis project came to be and evolved, what its main objectives and achievements have been, and how the project benefited its participants. The paper then summarizes the main learnings of the Apheis project.